A review of manufacturing resources planning models under different uncertainties: State-of-the-art and future directions - Wazed, M.A.; Ahmed, S.; Nukman, Y. (2010)
The main purposes of this paper are to enhance the understanding of manufacturing resources planning models under uncertain conditions by documenting the current state of affairs, and to stimulate a fruitful future research direction by identifying gaps between the relevant issues and the literature available in reputable journals. This paper is a comprehensive and up-to-date review of the existing literature on manufacturing resource planning models under uncertainty. The authors have found that the combined effects/impacts of the uncertainty factors on the system parameters have yet to be thoroughly studied. So far no research has been conducted into developing mathematical model(s) to study the uncertainty issues holistically in multi-period, multiple product, and multi-stage environments for manufacturing resources planning in association with commonality.